O IDOSO NA WEB: a concepção de uma identidade mercadológica no espaço discursivo publicitário da marca Plenitud na Internet. - CIRILLO, MARCO ANTONIO (2019)
The aging of the Brazilian population has several dimensions and difficulties, so nothing is fairer than to guarantee the elderly their integration into the community, either through consumption or access to technologies. Given this approach, this study sought to identify the relationship of the elderly with the Internet; if for him this space is not just a fad, it is not just used to demonstrate that he is inserted in the digital world, but to become an active consumer /customer/user/citizen. For this we used the methodological strategies constituted by the observations and transcriptions in a Focus Group and individual interviews with the elderly of the Aquarela Program - UMESP, completing with the discourse analysis of the virtual spaces presented to the participants. The corpus selected to perform this research was built with cutouts from the Plenitud website and Facebook page, specifically Plenitud Protect Plus disposable underwear. The survey revealed the longings of these audiences, bringing out the pleasure of using the Internet, becoming more participatory, feeling younger, confirming our hypotheses.